Scientific Literacy Instrument In Indonesia: A Systematic Literature Review Using Prisma - Lidwina Tae; Lucky Nindi Riandika Marfu’i; Feliksitas Angel Masing; I Wayan Sukarjita (IQRO: Journal of Islamic Education, 2025)
The research topic about scientific literacy assessment has become the concern of many scientists recently, including Indonesian researchers. This study aims to conduct a systematic literature review about scientific literacy instrument research in Indonesia for the last 24 years. This research used Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) to identify and screen the articles to be reviewed. In the initial stage, as many as 3,926 articles were found in the database of Google Scholar using several related keywords. Using 7 inclusion criteria that have been determined in the screening process, 102 articles were selected to be reviewed by the researchers in this study. It was found that research on scientific literacy instruments in Indonesia has been growing massively in recent years, with the majority of respondents coming from the western part of Indonesia, making students from the central and eastern areas underrepresented. Reflecting on these findings, challenges and opportunities will be discussed in this paper, along with the suggestion for future research.